Correlation-based network analysis of cancer metabolism A new systems biology approach in metabolomics - Armitage, Emily G.; Kotze, Helen L.; Williams, Kaye J. (SpringerBriefs in Systems Biology,, 2014)
With the rise of systems biology as an approach in biochemistry research, using high throughput techniques such as mass spectrometry to generate metabolic profiles of cancer metabolism is becoming increasingly popular. There are examples of cancer metabolic profiling studies in the academic literature; however they are often only in journals specific to the metabolomics community. This book will be particularly useful for post-graduate students and post-doctoral researchers using this pioneering technique of network-based correlation analysis. The approach can be adapted to the analysis of any large scale metabolic profiling experiment to answer a range of biological questions in a range of species or for a range of diseases.